2010
DOI: 10.1111/j.1365-2036.2010.04280.x
|View full text |Cite
|
Sign up to set email alerts
|

Depression and treatment with antidepressants are associated with the development of gastro‐oesophageal reflux disease

Abstract: SUMMARY BackgroundThe roles of depression and antidepressants in triggering reflux symptoms remain unclear.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
51
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(55 citation statements)
references
References 29 publications
4
51
0
Order By: Relevance
“…In a population-based case-control study investigating the risk of reflux esophagitis with the use of tricyclic antidepressants, it was demonstrated that the use of clomipramine increased GERD risk 4.8 times (OR: 4.82, 95% CI 2.08-11.14); no risk increase occurred with the use of other TCAs (29). No risk increase for GERD was found with the use of SSRI and SNRI antidepressants (28). In a manometry study in which the use of citalopram and a placebo were compared in 10 healthy adults, citalopram was shown not to cause a change in basal esophageal parameters (30).…”
Section: Antidepressant Drugsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a population-based case-control study investigating the risk of reflux esophagitis with the use of tricyclic antidepressants, it was demonstrated that the use of clomipramine increased GERD risk 4.8 times (OR: 4.82, 95% CI 2.08-11.14); no risk increase occurred with the use of other TCAs (29). No risk increase for GERD was found with the use of SSRI and SNRI antidepressants (28). In a manometry study in which the use of citalopram and a placebo were compared in 10 healthy adults, citalopram was shown not to cause a change in basal esophageal parameters (30).…”
Section: Antidepressant Drugsmentioning
confidence: 99%
“…TCAs have anticholinergic effects, and they reduce LESP. In a case-control study conducted by Martín-Merino et al (28), the risk of GERD in patients treated with TCAs was higher than in those not taking TCAs (statistically significantly higher even when all factors were corrected); also, it was shown that as the duration of TCA use increased, the risk of GERD also increased (while the odds ratio was 1.48 (95% CI 1.07-2.06) in patients using TCAs for 3 months or less, it was 2.06 (95% CI 1.43-2.97) in patients using TCAs for more than 3 months). Moreover, this effect is particularly evident with the use of amitriptyline, a TCA drug.…”
Section: Antidepressant Drugsmentioning
confidence: 99%
“…SIRS, We read with interest the recent article by Martin-Merino et al 1 The conclusion that the incidence of gastro-oesophageal reflux disease (GERD) was higher in patients with depression than in those without should be interpreted with caution because of ascertainment bias and an imprecise definition of GERD. Although depression could hypothetically increase the incidence of GERD diagnosis, we propose that the relationship between GERD and depression is based primarily on symptom ascertainment.…”
Section: Ascertainment Bias Increases Estimate Of Risk Of Gerd In Depmentioning
confidence: 94%
“…Moreover, most of these studies diagnosed psychological distress based on medical records or self-reported symptom scales, whereas other studies did not document the diagnosis of reflux with objective testing, rather making the diagnosis of reflux based on the patient's complaint or on medical history [22,23,24,25,26,27]. Thus, the results of these studies could have potential biases related to lack of proper diagnosis of either psychological disorders or reflux problems.…”
Section: Discussionmentioning
confidence: 99%